Growing Job Insecurity and Inequality between Good Jobs and Bad Jobs: An Interview with Arne Kalleberg - Arne Kalleberg (Journal of Economic Sociology, 2014)
Arne Kalleberg was interviewed by Tatiana Karabchuk and Andrey Shevchuk, senior fellows at the Higher School of Economics. This interview was conducted during the international conference “Embeddedness and Beyond: Do Sociological Theories Meet Economic Realities?” (Moscow, 25–28 October 2012), where Prof. Kalleberg presented his new research “The Growth of Precarious Work: A Challenge for Economic Sociology” In the interview Arne Kalleberg clarified the difference between job security and job stability and explained why it is better to draw a distinction between job security and employment security instead. Additionally, Prof. Kalleberg accounted for the growth of nonstandard employment and put this concept into historical context. Prof. Kalleberg stressed consequences of this tendency for both individuals and organizations. As a contribution to existing theoretical debate on this theme, Prof. Kalleberg suggested his own notion of “flexicurity”. Flexicurity is a meta-policy, combining greater flexibility for employers and protections for workers.